Holy Russia, sacred Israel : Jewish-Christian encounters in Russian religious thought - Rubin, Dominic, 1972- (Boston : Academic Studies Press, 2010)
"Holy Russia, Sacred Israel examines how Russian religious thinkers, both Jewish and Christian, conceived of Judaism, Jewry and the 'Old Testament' philosophically, theologically, and personally at a time when the Messianic element in Russian consciousness was being stimulated by events ranging from the pogroms of the 1880s through two Revolutions and World Wars to exile in Western Europe. An attempt is made to locate the boundaries between the Jewish and Christian, Russian and Western, Gnostic-pagan and Orthodox elements in Russian thought in this period. The author reflects personally on how the heritage of these thinkers, little analyzed or translated in the West, can help Orthodox (and other) Christians respond to Judaism (including "Messianic Judaism"), Zionism, and Christian antisemitism today."
Soloviev's Judeo-Russian wisdom -- Bulgakov and the sacred blood of Jewry -- N. Berdyaev, M. Gershenzon, and L. Shestov -- Vasily Rozanov (and Pavel Florensky) -- L. Karsavin and A. Steinberg : Russia and Israel symphonically -- Semyon Frank : from Russkiy yevrei to Russkiy yevropeetz -- Conclusion : Soloviev's heirs : the third generation -- Conclusion : Russian orthodoxy and Jewish-Christian dialogue : a note.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Judaism -- Russia -- History; Judaism -- Soviet Union -- History; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Russia -- Religion; Soviet Union -- Religion; RELIGION -- Judaism -- History; Christianity; Interfaith relations; Judaism; Religion; Russia; Soviet Union; RELIGION / Philosophy; Electronic books; History